The Burden of Anemia in Pregnancy Among Women Attending the Antenatal Clinics in Mkuranga District, Tanzania - Ngimbudzi, Evelyine B.; Massawe, Siriel N.; Sunguya, Bruno F. (Frontiers in Public Health, 2021)
Abstract Background: The burden of anemia in pregnancy is of global health importance. Tanzania is no exception. It varies from one region to another owing to the differences in causes, but overall causing a significant burden of maternal mortality. This study sought to assess the prevalence and factors associated with anemia among pregnant women attending antenatal clinic (ANC) at Mkuranga district in Pwani region of Tanzania Methods: This cross-sectional study design was conducted among 418 pregnant women aged 15-49 years attending the Mkuranga district hospital and Kilimahewa health centre. The outcome variable of interest was anemia in pregnancy defined as haemoglobin concentration of 13g/dl. Data was collected using face to face interviews with a standardized pretested questionnaire, and through blood samples collected for haemoglobin testing. Descriptive analysis was used to determine the prevalence of anemia while multiple logistic regression was used to determine factors associated with anemia in pregnancy. Results: Anemia was prevalent among 83.5% of pregnant women attending the two major antenatal clinics in Mkuranga district were anemic. Of them, 29% presented with mild anemia, while 62% had moderate anemia, and 0.09% succumbed to severe anemia. Factors associated with anemia included being in the third trimester [AOR=2.87, p=0.026]; not consuming vegetables (AOR=2.62, p=0.008), meat (AOR=2.71, p=0.003), eggs (AOR=2.98, p=0.002), and fish (AOR=2.38, p=0.005). Conclusion: More than eight in ten pregnant women attending ANC in Mkuranga districts were anemic. Such unprecedented burden of anemia is associated with a number of factors including feeding practices such as not consuming iron-rich foods like vegetables, meat, eggs, and fish. Women in their third trimester were also more likely to suffer from anemia. This unprecedented burden of anemia in pregnancy can be addressed if efforts to improve feeding practices and early monitoring at the antenatal clinics are sustained.